What is the radius of a circle with the equation x2 + y2 – 14x + 10y = 250?

Answers

X2 + y2 - 14x + 10y = 250
x2 -14x + 49 - 49 + y2 + 10x + 25 - 25 = 250
(x - 7)^2 - 49 + (y+5)^2 - 25 = 250
(x-7)^2 + (y+5)^2 = 250 + 49 + 25
(x-7)^2 + (y+5)^2 = 324

Therefore the radius, r
r = 324^0.5
r = 18
The radius is 18, i didnt do the work because i followed the same proscess ^
First, we have to change the General equation in to standard equation:
Equation: x^2 + y^2 − 14x + 10y = 250 
1) x^2 − 14x + y^2 + 10y = 250 
2) x^2 − 14x + (-14/2)^2 + y^2 + 10y + (10/2)^2 = 250 + (-14/2)^2 + (10/2)^2 
3) (x − 7)^2 + (y + 5)^2 = 324 
4) (x − 7)^2 + (y + 5)^2 = 18^2 

 Radius =18 units
Complete the square .

x^2-14x = (x-7)^2-(-7)^2 
             = (x-7)^2-49
y^2+10y = (x+5)^2-(5)^2
              =(x+5)^2-25
(x-7)^2+(y+5)^2-49-25=250
(x-7)^2+(y+5)^2=324
                         =sqrt 324
                         =18

Option (d) is correct.

Radius of given equation is 18 units.

Step-by-step explanation:

Given : The equation of circle as x^2+y^2-14x+10y=250

We have to find the radius of given circle.

Consider the given equation of circle x^2+y^2-14x+10y=250

The standard equation of circle with center (h,k) and radius r is given as

(x-h)^2+(y-k)^2=r^2

Rewriting in standard form, we have,

Grouping x and y variables, we have,

\left(x^2-14x\right)+\left(y^2+10y\right)=250

Convert x terms to perfect square term by adding 49 both side, we have,

\left(x^2-14x+49\right)+\left(y^2+10y\right)=250+49

Simplify, we have,

\left(x-7\right)^2+\left(y^2+10y\right)=250+49

Convert y  terms to perfect square term by adding 25 both side, we have,

\left(x-7\right)^2+\left(y^2+10y+25\right)=250+49+25

Simplify, we have,

\left(x-7\right)^2+\left(y+5\right)^2=324

Thus, standard form is

\left(x-7\right)^2+\left(y-\left(-5\right)\right)^2=18^2

Thus, radius of given equation is 18 units.

D

Step-by-step explanation:

To find the radius of the circle with equation x2 + y2 – 14x + 10y = 250, convert the equation into vertex-form (x - h)² + (y-k)² = r². Convert by completing the square for x² - 14x and y² + 10y.

Complete the square by dividing each term -14x and 10y in two. Then square each.

-14/2 = -7 and -7² = 49

10/2 = 5 and 5² = 25

The equation becomes x² - 14x + 49 + y² + 10y + 25 = 250 + 49 + 25.

We simplify the equation into (x-7)² + (y + 5)² = 324.

324 is the value of radius squared. Take the square root to find the radius.

√324 = 18

The radius is 18 units.

18

Step-by-step explanation:

x^2 + y^2 – 14x + 10y = 250

x^2 -14x + y^2 + 10y = 250

x^2 - 14x + (-7)^2 + y^2 + 10y + (5)^2 = 250 + (-7)^2 +  (5)^2

(x-7)^2 + (y + 5)^2 = 250 + 49 + 25

(x-7)^2 + (y + 5)^2 = 324

Comparing with the general circle (x - b)^2 + (y - a)^2 = r^2

we have; r^2 = 324

               r = square root(324)

                r = 18

18

Step-by-step explanation:

x^2 + y^2 – 14x + 10y = 250

x^2 -14x + y^2 + 10y = 250

x^2 - 14x + (-7)^2 + y^2 + 10y + (5)^2 = 250 + (-7)^2 +  (5)^2

(x-7)^2 + (y + 5)^2 = 250 + 49 + 25

(x-7)^2 + (y + 5)^2 = 324

Comparing with the general circle (x - b)^2 + (y - a)^2 = r^2

we have; r^2 = 324

               r = square root(324)

                r = 18



Do you know the answer?

Other questions on the subject: Mathematics

Mathematics, 21.06.2019, jayy2x41
 A.Placing different groups of people in different colored rooms and recording their mood Step-by-step explanation:An observational study is a study in which a researcher just rec...Read More
3 more answers
3. (5x + 1) - (-10x + 6)simplify the answer choice. combine like terms. remember to distribute the negative to the terms inside the second parenthesis. also remember that two negat...Read More
1 more answers
191 students play sports and ninety-seven 10th graders were surveyed.step-by-step explanation:...Read More
1 more answers
[tex]35 = 45 - n[/tex]put like terms together.[tex]n = 45 - 35[/tex]or[tex]35 - 45 = - n[/tex]remember that the 45 becomes negative when moved to the other side.[tex]n = 10[/tex]or...Read More
1 more answers
2x + y = 9x + y = 6To graph, rewrite in y=mx+b formy = -2x + 9 (slope -2, y-intercept 9)y = -x + 6 (slope -1, y-intercept 6)Once you graph you will see that the point of intersecti...Read More
1 more answers